Economic feasibility analysis and environmental impact assessment for the comparison of conventional and microwave torrefaction of spent coffee grounds. (January 2023) - Zhang, Congyu; Chen, Wei-Hsin; Ho, Shih-Hsin
Abstract: Biomass torrefaction is a promising method for carbon-neutral solid biofuel production. The economic feasibility and environmental pollution potential of the torrefaction operation are of great concern to developing a sustainable energy system. In this study, spent coffee grounds are selected as the feedstocks for comparing the economic feasibility of different torrefaction methods and evaluating the environmental pollution potential of conventional torrefaction and microwave torrefaction. The result shows that microwave torrefaction possesses a more economically efficient approach for biomass upgrading, as a result of lower energy input and carrier gas consumption. For environmental impact assessment, several different indicators are adopted for evaluating the torrefaction process, which is based on openLCA software of CML 2001 method. The life cycle assessment results indicate that the environmental impact of microwave torrefaction is lower than conventional torrefaction, especially when torrefied at light conditions. Thus, microwave light torrefaction is the optimal condition for spent coffee grounds upgrading. However, the growth rate of the environmental impact of microwave torrefaction is greater than conventional torrefaction, including resource depletion and terrestrial ecotoxicity. Moreover, the environmental impact of the torrefaction process is strongly correlated to the torrefaction severity. Graphical abstract: Image 1 Highlights: Microwave light torrefaction is energy-saving for fuel upgrading. Microwave torrefaction saves expenses of biochar production. The eco-invent 3.4 databases of openLCA with the CML 2001 method are adopted. Microwave torrefaction is more feasible than conventional torrefaction. Microwave light torrefaction possesses a lower environmental impact.